Pemanfaatan Ikan Rucah: Mempersiapkan Wirausaha Baru dalam Produksi Abon Ikan “Bon-Bon” sebagai Alternatif Pemberian Makanan Tambahan (PMT) Lokal - Meirina Dwi Larasati; Kun Aristiati Susiloretni; Sri Noor Mintarsih; Yuwono Setiadi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2023)
Nutrition of pregnant women plays an important role in the growth of the fetus and the delivery process. Malnutrition during pregnancy increases fetal growth retardation, low birth weight, and risk of stunting at 2 years of age. One of the national strategies for accelerating stunting reduction in the form of specific interventions is that pregnant women with Chronic Energy Deficiency receive Supplementary Feeding. Currently, the provision of PMT to pregnant women is in the form of layer biscuits formulated with vitamins and minerals. Other types of supplementary food as recovery food include animal protein source foods that are given for 90 days. Local PMT needs to be developed to support healthy eating patterns from a sustainable food system using local and inexpensive food ingredients such as trash fish. The purpose of this activity is to prepare new independent entrepreneurs in utilizing local food ingredients as an alternative to local PMT for pregnant women in KEK through training on making shredded fish for posyandu and UMKM cadres in Pedurungan Tengah Village totaling 21 people. The results of the training still need to improve the taste and texture of the shredded fish that has been processed by the participants. Suggestions for implementing the next activity is assistance during the manufacture of shredded fish so that local PMT products are obtained with good acceptance.